This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: Chapter 6 LINEAR CONVOLUTION Copyright c 1996 by Ali H. Sayed. All rights reserved. These notes are distributed only to the students attending the undergraduate DSP course EE113 in the Electrical Engineering Department at UCLA. The notes cannot be reproduced without written consent from the instructor: Prof. A. H. Sayed, Electrical Engineering Department, UCLA, CA 90095, firstname.lastname@example.org. The response of an LTI system with impulse response sequence h ( n ) to any input sequence x ( n ) is given by the convolution sum y ( n ) = x ( n ) ? h ( n ) = X k =- x ( k ) h ( n- k )] In this chapter we study more closely such convolution sums and derive several of their properties. We shall also provide some physical interpretations for the properties of the convolution sum. Properties of the Convolution Sum 1. Commutativity . It holds that x ( k ) ? h ( k ) = h ( k ) ? x ( k ) That is, X k =- x ( k ) h ( n- k ) = X k =- h ( k ) x ( n- k ) Proof: Introduce the new variable j = n- k . Then X k =- x ( k ) h ( n- k ) = X j =- x ( n- j ) h ( j ) . Rename j as k again to obtain X j =- x ( n- j ) h ( j ) = X k =- h ( k ) x ( n- k ) . Physical interpretation. Think of x ( n ) and h ( n ) as the impulse-response sequences of two LTI systems. Consider further the series cascades: ( n ) x ( n ) h ( n ) y 1 ( n ) 49 50 Linear Convolution Chapter 6 ( n ) h ( n ) x ( n ) y 2 ( n ) The impulse response of the first cascade is y 1 ( n ) = x ( n ) ? h ( n ) (as established in Chapter 5). On the other hand, the impulse response of the second cascade is y 2 ( n ) = h ( n ) ? x ( n ). By the commutativity property, both output sequences must agree, y 1 ( n ) = y 2 ( n ). Therefore, the commutativity property tells us that we can always switch the order of LTI systems in a series cascade. 2. Distributivity . The following relations hold: x ( n ) ? [ h 1 ( n ) + h 2 ( n )] = x ( n ) ? h 1 ( n ) + x ( n ) ? h 2 ( n ) and [ x 1 ( n ) + x 2 ( n )] ? h ( n ) = x 1 ( n ) ? h ( n ) + x 2 ( n ) ? h ( n ) Algebraic proof: We prove the first relation. An identical argument applies to the second one. Using the definition of convolution we write x ( n ) ? [ h 1 ( n ) + h 2 ( n )] = X k =- x ( k )[ h 1 ( n- k ) + h 2 ( n- k )] = X k =- x ( k ) h 1 ( n- k ) + X k =- x ( k ) h 2 ( n- k ) = x ( n ) ? h 1 ( n ) + x ( n ) ? h 2 ( n ) . Physical interpretation. Consider two LTI systems with impulse responses h 1 ( n ) and h 2 ( n ) and assume they are connected in parallel, as shown in Fig. 6.1. x ( n ) h 1 ( n ) h 2 ( n ) y ( n ) Figure 6.1. Parallel connection of two LTI systems. Let x ( n ) be the input sequence to this cascade connection. We know from Chapter 5 that the impulse response sequence of the parallel connection is h 1 ( n )+ h 2 ( n ). There- fore, the output of the system will be x ( n ) ? [ h 1 ( n ) + h 2 ( n )]. On the other hand, the output of h 1 ( n ) is x ( n ) ? h 1 ( n ) and the output of...
View Full Document